A Themed Issue in Memory of Academician Duzheng Ye (1916-2013) - Zou, Xiaolei; Wu, Guoxiong; Tan, Zhemin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Topic in memory of Academician Duzheng Ye (1916-2013) was written on the tenth anniversary of Professor Ye's passing. It comprises 31 original research manuscripts and reviews spanning atmospheric dynamics and physics, synoptic weather patterns, climate change, and remote sensing observations for weather and climate. It represents a collective dedication and expertise from 30 esteemed invited authors and their collaborators who hold Prof. Ye in high regard. This Topic serves a dual purpose to not only pay homage to Professor Ye's academic legacy but also transmit their admiration for him to the forthcoming generations.